Effects of vertebrates, insects, and pathogens on patterns of early plant recruitment in tropical forests. - Beckman, Noelle Gabriele (My University, 2010)
Vertebrate seed dispersers and seed predators, insect seed predators, and pathogens are known to influence plant survival, population dynamics, and species distributions. The selective pressure of these mutualists and antagonists have resulted in a myriad of plant adaptations, including morphological and nutritional fruit traits to attract seed dispersers, and plant defenses to deter seed predators and pathogens. The importance of vertebrates, insects, and pathogens for plant communities has long been recognized, but their absolute and relative importance in early recruitment of multiple coexisting tropical plant species has not been quantified. Further, little is known about the relationship of fruit traits to seed dispersal and natural enemy induced seed and seedling mortality in tropical plants. My dissertation investigates the importance of these groups of organisms in the sequential stages of early plant recruitment (i.e. from fruit developing in the crown to seedlings on the ground) in tropical forests. I used a combination of empirical and theoretical studies: an experimental study of pre-dispersal seed mortality in plant canopies of seven species, a bioassay experiment examining patterns of fruit toxicity for eleven species, a simulation study of the interacting effects of seed dispersal and enemy attack on spatial patterns of surviving seedlings in theory, and a field study of the effects of partial defaunation of vertebrates (by hunting) on pre-dispersal seed predation and seed removal in two tree species. To determine the influences of vertebrates, insects, and pathogens on reproduction of plants varying in fruit traits, I investigated reductions in fruit development and seed germination due to vertebrates, insects, and fungal pathogens through experimental removal of these enemies using canopy exclosures, insecticide, and fungicide, respectively at the Canopy Crane Access System in Parque Natural Metropolitano in Central Panama. Results suggest that predispersal seed mortality is attributable to different natural enemies in different canopy species. Fruit morphology explained some of the interspecific variation in fruit development and seed survival in response to natural enemy removal treatments. This is the first experimental test of the relative effects of vertebrates, insects, and pathogens on seed survival in the canopy. To investigate patterns of fruit toxicity, I used bioassays involving brine shrimp (Artemia franciscana) and two foliar fungal pathogens (Fusarium sp, Phoma sp.) to understand how chemical defenses of coexisting canopy plants differ from the immature to the mature stage of fruit development and between the seed and pericarp. Every plant species tested in this study exhibited toxicity to at least one bioassay organism but patterns of toxicity depended on plant species and bioassay organism. To explore how patterns of natural enemy attack and seed dispersal affect seedling recruitment patterns, I developed a spatially-explicit, individual-based model to study plant life stages following seed dispersal. With this model, I explored how different seed deposition patterns and natural enemies affect the spatial patterns of surviving seedlings in a simulated model community. The seedling recruitment patterns observed in the model reproduced the range of patterns observed empirically. Recruitment patterns were sensitive to the type of natural enemy attack and the movement distances and fecundity of natural enemies, as well as to seed dispersal distances and the degree of clumping. To investigate how hunting alters seed dispersal and seed predation, I compared these processes for two canopy tree species that differ 16-fold in seed size in both hunted and protected forests in Central Panama. The results of this study suggest that in hunted areas there are greater reductions in seed removal and seed predation of the larger-seeded compared to the smaller-seeded tree. Overall, the results of my dissertation contribute to an emerging, but still very incomplete, trait-based approach to understanding interspecific variation in biotic interactions. Determining the relative roles of vertebrates, insects, and pathogens throughout the stages of plant recruitment will aid in our understanding of the mechanisms that limit plant populations, contribute to our knowledge of diversity maintenance, and is critical to predicting the consequences of anthropogenic pressures on plant communities.
University of Minnesota Ph.D. dissertation. July 2010. Major: Ecology, Evolution and Behavior. Advisors: Helene Muller-Landau, Claudia Neuhauser. 1 computer file (PDF); xiii, 155 pages.
Keywords: Community ecology; Hunting; Janzen-Connell; Predispersal; Theoretical ecology; Toxicity; Ecology, Evolution and Behavior